Valorization of solid waste in subsurface flow constructed wetlands based on renewable modular structures: A contribution to a circular economy - Pinho, Henrique J. O. (2021)
In this chapter, a case study is used as a basis for discussion of the contribution of constructed wetlands (CWs) to circular economy and to sustainable development. Although CWs already represent a sustainable and green technology for wastewater treatment, this study aimed to enhance CW potential to fit the circular economy paradigm. The main purpose of the study was the use of renewable materials and solid waste in the design of modular CWs. A modular pilot-scale CW was built in a wood-based structure with a filling media consisting of a mixture of three solid waste materials. This approach represents an example of the potential contribution of CWs to a circular economy through a shorter circuit for water reuse and their integration into longer economic circuits, which can be closed by symbiosis with other processes and industrial activities such as the valorization of solid waste and wood for CW assembly.